Solvation dynamics and microheterogeneity in deep eutectic solvents - Chatterjee, Srijan; Chowdhury, Tubai; Bagchi, Sayan (Journal of Physical Chemistry B, 2024)
Deep eutectic solvents have attracted considerable attention due to their unique properties and their potential to replace conventional solvents in diverse applications, such as catalysis, energy storage, and green chemistry. However, despite their broad use, the microscopic mechanisms governing solvation dynamics and the role of hydrogen bonding in deep eutectic solvents remain insufficiently understood. In this article, we present our contributions toward unravelling the micro heterogeneity within deep eutectic solvents by combining vibrational Stark spectroscopy and two-dimensional infrared spectroscopy with molecular dynamics simulations. Our findings demonstrate how the composition, constituents, and addition of water significantly influence the heterogeneous hydrogen bonding network and solvent dynamics within these systems. These insights provide valuable guidance for the design of next-generation solvents tailored to specific applications. By integrating experimental and computational approaches, this work sheds light on the intricate relationship between solvation dynamics and nanostructure in deep eutectic solvents, ultimately paving the way for innovative advances in solvent design.